Amalan Hisbah Dan Prospek Terhadap Pengurusan Akidah Di Malaysia: Satu Tinjauan Awal: The Practice of Hisbah and Prospects for the Management of Faith in Malaysia: An Initial Review - Rambli, Sophian Bin; Alwi, Engku Ahmad Zaki Engku; Fauji, Imam (Universitas Muhammadiyah Sidoarjo, 2018)
This paper aims to review the practice of hisbah in Malaysia and the relationship with the management of aqidah in Malaysia. Second is to know for sure the role of Islamic institutions in the practice of hisbah especially in the management of faith in the issue and challenges in the inauguration of faith in Malaysia. This study uses content analysis to discuss deep in the practice of faith and its relationship to the management of faith in Malaysia. Although in Malaysia there are institutions such as the Position of the Progress of Islamic Malaysia (JAKIM), the State Islamic Religion Council (MAIN), the State Islamic Religion (JAIN) and the State Mufti Position (JMN) do not use the term hisbah, but intipati, implementation and function the function of hisbah is carried out by Islamic agencies concerned. This study method uses content analysis to get an initial review of the role and contribution of hisbah practice in Malaysia in the issue of the management of faith in Malaysia. And also the initial observations found elements and elements of the approach of hisbah practice are very necessary and implemented in the contemporary world to deal with issues and challenges include the management of aqidah which is emphasized as a fortress rather than threats that bring impact to the mistakes and renewal of the grip of Muslims in Malaysia. Then the role and application of hisbah practice in the management of the faith is very much needed special attention, there are governments, communities and individual Muslims so that the teachings of Islam are maintained and maintained in achieving the blessings and blessings of Allah SWT.